The Effects of an Increase in the Retirement Age on Health – Evidence from Administrative Data - Mara Barschkett; Johannes Geyer; Peter Haan; Anna Hammerschmid (Institute of Labor Economics (IZA), 2021)
This study analyzes the causal effect of an increase in the retirement age on health. We exploit a sizable cohort-specific pension reform for women using two complementary empirical approaches – a Regression Discontinuity Design and a Difference-in-Differences approach. The analysis is based on official records covering all individuals insured by the public health system in Germany and including all certified diagnoses by practitioners. This enables us to gain a detailed understanding of the multi-dimensionality in these health effects. The empirical findings reflect the multi-dimensionality but allow for deriving two broader conclusions. We provide evidence that the increase in the retirement age negatively affects health outcomes as the prevalence of several diagnoses, e.g., mental health, musculoskeletal diseases, and obesity, increases. In contrast, we do not find support for an improvement in health related to a prolonged working life since there is no significant evidence for a reduction in the prevalence of any health outcome we consider. These findings hold for both identification strategies, are robust to sensitivity checks, and do not change when correcting for multiple hypothesis testing.
Keywords: I10; I12; I18; J14; J18; J26; 330; Germany; retirement; pension reform; health; ICD-10; Regression Discontinuity Design; Difference-in-Differences